Carbon Monoxide-Releasing Molecule-2 Reduces Intestinal Epithelial Tight-Junction Damage and Mortality in Septic Rats. - Shulong Zhang; Shuyun Zheng; Xin Wang; Qiankun Shi; Xiang Wang; Shoutao Yuan; Guozheng Wang; Zhenling Ji (PLoS ONE)
Objective Damage to intestinal epithelial tight junctions plays an important role in sepsis. Recently we found that Carbon Monoxide-Releasing Molecule-2 (CORM-2) is able to protect LPS-induced intestinal epithelial tight junction damage and in this study we will investigate if CORM-2 could protect intestinal epithelial tight junctions in the rat cecal ligation and puncture (CLP) model. Materials and methods The CLP model was generated using male Sprague-Dawley (SD) rats according to standard procedure and treated with CORM-2 or inactive CORM-2 (iCORM-2), 8 mg/kg, i.v. immediately after CLP induction and euthanized after 24h or 72h (for mortality rate only). Morphological changes were investigated using both transmission electron and confocal microscopy. The levels of important TJ proteins and phosphorylation of myosin light chain (MLC) were examined using Western blotting. Cytokines, IL-1β and TNF-α were measured using ELISA kits. The overall intestinal epithelial permeability was evaluated using FD-4 as a marker. Results CORM-2, but not iCORM-2, significantly reduced sepsis-induced damage of intestinal mucosa (including TJ disruption), TJ protein reduction (including zonula occludens-l (ZO-1), claudin-1 and occludin), MLC phosphorylation and proinflammatory cytokine release. The overall outcomes showed that CORM-2 suppressed sepsis-induced intestinal epithelial permeability changes and reduced mortality rate of those septic rats. Conclusions Our data strongly suggest that CORM-2 could be a potential therapeutic reagent for sepsis by suppressing inflammation, restoring intestinal epithelial barrier and reducing mortality.